2005
DOI: 10.1002/ajmg.a.30360
|View full text |Cite
|
Sign up to set email alerts
|

Gracile bones, periostal appositions, hypomineralization of the cranial vault, and mental retardation in brothers: Milder variant of osteocraniostenosis or new syndrome?

Abstract: We report on two brothers with ossification anomalies of membranous and cranial bones, remodeling defect of long bones leading to dense, overtubulated, narrow diaphyses, metaphyseal flare, periostal hyperosotosis that increased during the first months of life, thoracic dystrophy and severe hypotonia. One boy had hypospadias and cleft palate. Follow-up of the surviving boy documented progressive osteopenia, slow healing of the periostal anomalies, liver angiomatosis, mental and motor delay, thoracic deformity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Overall, whenever prenatal ultrasound was performed, the most prominent clinical features detected were a cloverleaf-shaped skull (11 out of 17 cases with at least one sonography reported), IUGR (15/17 cases), limb undergrowth (16/17 cases) and occasionally intrauterine bone fractures (7/17 cases) [ 3 , 4 , 22 , 23 , 24 , 25 , 26 , 28 , 29 ]. Most of these features were already apparent at 20 weeks of gestation (cfr.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, whenever prenatal ultrasound was performed, the most prominent clinical features detected were a cloverleaf-shaped skull (11 out of 17 cases with at least one sonography reported), IUGR (15/17 cases), limb undergrowth (16/17 cases) and occasionally intrauterine bone fractures (7/17 cases) [ 3 , 4 , 22 , 23 , 24 , 25 , 26 , 28 , 29 ]. Most of these features were already apparent at 20 weeks of gestation (cfr.…”
Section: Discussionmentioning
confidence: 99%
“…Patients 3 and 4 likely represent much milder cases of osteocraniostenosis but could represent a distinct disorder. Recently, Verloes et al 2005 reported two brothers with radiologic anomalies that included overtubulated long bones with metaphyseal flare and diaphyseal thinning as well as ossification anomalies of membranous and cranial bones and discussed some of the similar findings of these siblings to patients with osteocraniostenosis. The authors suggested autosomal recessive or X‐linked inheritance.…”
Section: Discussionmentioning
confidence: 99%
“…OCS (OMIM #602361) presents with a more severe, perinatal lethal phenotype characterized by hypomineralized skull frequently resulting in cloverleaf shape, large anterior fontanelle, hypoplastic or absent spleen, and gracile ribs and long bones with wide metaphyses (Costa et al, 1998; Elliott et al, 2006; Puvabanditsin et al, 2016; Spear, 2006; Unger et al, 2013; Verloes et al, 2005). Facial features include prominent forehead, short philtrum and nose, depressed nasal bridge, low‐set ears, midface hypoplasia and small, inverted V‐shape mouth, an ophthalmological abnormalities such as microphthalmia (Beluffi, 2013; Elliott et al, 2006; Puvabanditsin et al, 2016).…”
Section: Introductionmentioning
confidence: 99%